Familial high myopia – challenge of modern genetics - Adamiec, Joanna; Niżankowska, Maria Hanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
In this paper has been accomplished an estimation of contemporary achievement in mollecular researches domains of pathology in familial high myopia. Clinical observations of monozygotic and dizygotic twins groups and also among family members with this type of myopia disclosing in following generations show, that it has inborn character. Nowadays, it has been identified three gen locci connected with heritage of this illness unit: 18p11.31,12q21-31,7q36. Above incontestable achievements do not interpret mechanism uprising this disease. Problem is still, to define the products planned by exchanged area of DNA, conditioning progress of high familial myopia.